STUDY OF THE MULTIPLICITY OF HADRONS ON NUCLEI - L. Grigoryan
Improved two-scale model with symmetric Lund distribution function is used to perform the fit to semi-inclusive deep-inelastic scattering (SIDIS) data on nuclear targets of HERMES experiment at DESY. The ratio of hadron multiplicity on nuclear target to the deuterium one is chosen as observable, as usually. Some peculiarities of the fit are discussed. The two-parameter’s fit gives satisfactory agreement with the data. The results of the present and previous fits are compared.
Keywords: Physics; Nuclear physics